Developing a pmri-based learning design for social arithmetic through online buying and selling contexts - Oktalina, Dian; Widiawati; Lismareni, Neni (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
Social arithmetic is closely related to students’ daily economic activities; however, many students experience difficulties in understanding its concepts due to the abstract presentation of learning materials. This study aimed to develop a Hypothetical Learning Trajectory (HLT) based on the Indonesian Realistic Mathematics Education (PMRI) approach by utilizing online buying and selling as a learning context. The study employed a design research methodology of the developmental research type within a qualitative framework. The research was conducted through three phases: preparing for the experiment, design experiment, and retrospective analysis. Participants were seventh-grade students at SMP Muhammadiyah Pagaralam during the 2024/2025 academic year. Data were collected through classroom observations, interviews, document analysis, and pre- and post-tests. The results indicate that the developed HLT effectively supports students in constructing a meaningful understanding of social arithmetic concepts, such as discounts, taxes, and final costs, through contextual and experiential learning activities. The PMRI-based learning design also encourages active student participation and supports the development of critical thinking skills. These findings suggest that the proposed learning trajectory can serve as a practical reference for designing context-based social arithmetic instruction.